Consuming fermented distillers' dried grains with solubles (DDGS) feed reveals a shift in the faecal microbiota of growing and fattening pigs using 454 pyrosequencing - Jin WANG; Ye HAN; Jin-zhao ZHAO; Zhi-jiang ZHOU; Huan FAN (Journal of Integrative Agriculture)
The objective of this study was to investigate pig fed by Bacillus coagulans-fermented distillers' dried grains with solubles (DDGS) on the faecal microbial composition and diversity using 454 pyrosequencing. Healthy crossbred (Duroc×Yorkshire×Landrace) growing and fattening pigs (n=48), with an average initial body weight of 65 kg, were divided into two groups (24 replicates per group; four pens per group; six pigs per pen), and given either DDGS feed as the control, or B. coagulans-fermented DDGS feed as the treatment. Faecal samples were collected on day 0, 7, 14, 21, and 28. DNA was extracted, and the V3–V6 region of the 16S rRNA gene was amplified. The fermented DDGS feed affected the relative abundance of bacteria populations at the phylum, genus, and species levels. At the genus level, the consumption of fermented DDGS feed led to higher relative abundances of faecal Prevotella, Lactobacillus, Clostridium, Bifidobacterium, Roseburia, and Bacillus, and lower relative abundances of faecal Escherichia, Ruminococcus, Dialister, unclassified Lachnospiraceae, unclassified Ruminococcaceae, and unclassified Enterobacteriaceae than in the control. At the species level, the consumption of fermented DDGS feed led to higher relative abundances of faecal Prevotella sp., Lactobacillus johnsonii, Lactobacillus fermentum, Lactobacillus mucosae, Lactobacillus reuteri, Clostridium butyricum, Bifidobacterium sp., and Roseburia sp., and lower relative abundances of faecal Prevotella copri, Escherichia coli, Ruminococcus gnavus, Ruminococcus flavefaciens, and Dialister sp. than in the control. Principal coordinates analysis indicated a distinct separation in the faecal microbial communities of pigs that were fed the fermented and unfermented DDGS feed. Fermented DDGS feed significantly increased the average daily gain (ADG) of pigs, and significantly decreased the average daily feed intake (ADFI) of feed and feed/gain (F/G). Thus, our results demonstrate a beneficial shift in the faecal microbiota of pigs consuming fermented DDGS feed, with potential applications in livestock production.